Feature : The diamond quantum revolution. (1st April 2020) - Markham, Matthew; Twitchen, Daniel
Abstract: Diamond is more than just a pretty gem – it has many attractive properties that stretch far beyond its aesthetic appeal. Matthew Markham and Daniel Twitchen explain how this special form of carbon now has many practical quantum applications too